A pH-responsive dissociable mesoporous silica-based nanoplatform enabling efficient dual-drug co-delivery and rapid clearance for cancer therapy. (14th May 2020) - He, Yongju; Shao, Linjie; Usman, Ibrahim; Hu, Yao; Pan, Anqiang; Liang, Shuquan; Xu, Hui
Abstract : A pH-responsive dissociable mesoporous silica-based cluster with efficient dual-drug co-delivery for combinational cancer therapy, tumor accumulation via its large size-favored EPR effect and rapid clearance by its acid-triggered dissociation. Abstract : The balance between tumor accumulation and renal clearance has severely limited the efficacy of mesoporous silica-based drug nanocarriers in cancer therapy. Herein, a pH-responsive dissociable mesoporous silica-based nanoplatform with efficient dual-drug co-delivery, tumor accumulation and rapid clearance for cancer therapy is achieved by adjusting the wetting of the mesoporous silica surface. At pH 7.4, the synthesized spiropyran- and fluorinated silane-modified ultrasmall mesoporous silica nanoparticles (SP-FS-USMSN) self-assemble to form larger nanoclusters (denoted as SP-FS-USMSN cluster) via hydrophobic interactions, which can effectively co-deliver anticancer drugs, doxorubicin hydrochloride (Dox) and curcumin (Cur), based on the mesopores within SP-FS-USMSN and the voids among the stacked SP-FS-USMSN. At pH 4.5–5.5, the conformational conversion of spiropyran from a "closed" state to an "open" state causes the wetting of the SP-FS-USMSN surface, leading to the dissociation of the SP-FS-USMSN cluster for drug release and renal clearance. The in vitro and in vivo studies demonstrate that the Cur and Dox co-loaded SP-FS-USMSN cluster (Cur-Dox/SP-FS-USMSN cluster) possesses great combined cytotoxicity, and can accumulate into tumor tissue by its large size-favored EPR effect and potently suppress tumor growth in HepG2-xenografted mice. This research demonstrates that the SP-FS-USMSN cluster may be a promising drug delivery system for cancer therapy and lays the foundation for practical mesoporous silica-based nanomedicine designs in the future.